2006
DOI: 10.2139/ssrn.950929
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Trade Agreements in Gravity Models: A Meta-Analysis

Abstract: Over the time a large number of reciprocal preferential trade agreements (RTAs) have been concluded among countries. Recently many studies have used gravity equations in order to estimate the effect of RTAs on trade flows between partners. These studies report very different estimates, since they differ greatly in data sets, sample sizes, and independent variables used in the analysis. So, what is the "true" impact of RTAs? This paper combines, explains, and summarizes a large number of results (1827 estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 93 publications
3
56
0
2
Order By: Relevance
“…Following the recent trend in meta-analysis (Disdier & Head, 2008;Doucouliagos & Stanley, 2009;Cipollina & Salvatici, 2010), we use all estimates reported in the studies. If we arbitrarily selected the "best" estimate from each study, we could introduce an additional bias, and if we used the average reported estimate, we would discard a lot of information.…”
Section: The Spillover Estimates Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the recent trend in meta-analysis (Disdier & Head, 2008;Doucouliagos & Stanley, 2009;Cipollina & Salvatici, 2010), we use all estimates reported in the studies. If we arbitrarily selected the "best" estimate from each study, we could introduce an additional bias, and if we used the average reported estimate, we would discard a lot of information.…”
Section: The Spillover Estimates Data Setmentioning
confidence: 99%
“…Such extreme values, most of which come from 5 For example, if the spillover regression is specified in the following form: ln Productivity ijt = e working papers and mimeographs, might lead to volatile results and degrade the graphical analysis. To account for outliers, some other large meta-analyses use the Grubbs test (Disdier & Head, 2008;Cipollina & Salvatici, 2010). But because we use precision to filter out publication bias, outlying values in precision could also invalidate the results.…”
Section: The Spillover Estimates Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there are numerous studies analyzing the economic impacts of RTAs [8] . RTAs might be expected to increase trade between partners, since cheaper import within the agreement may replace domestic production ("trade creation") or crowed out imports from the rest of the world ("trade diversion") [17,23] .…”
Section: Ecomentioning
confidence: 99%
“…First, it analyses the effect of TA institutional quality on international trade in a region-to-country dataset and in contrast to mainstream research, we then examine the institutional quality of TAs (Kohl et al 2013) rather than their creation per se (Cipollina, Salvatici 2010, Head, Mayer 2014. Second, it addresses the importance of dealing with within-country heterogeneity in a gravity framework when analysing the factors behind the variation in the IM and in the EM of trade.…”
Section: Introductionmentioning
confidence: 99%